Avaliação de plantadora de cana-de-açúcar com sulcador de desarme automático e rotação da esteira distribuidora - Compagnon, Ariel Muncio [UNESP] (2015)
A mechanized plantation of sugarcane must perform both operations furrow, fertilizer application, distribution of seedlings and mating of the furrows. Aimed to evaluate the prototype of a planter sugarcane on wheels, which features a new system for distributing wheels and furrow, depending on planting speed, the distributor belt speed and depth of furrow. In the first study, a randomized design was adopted, with two planting speeds (5.0 and 6.5 km h-1) and two rotations of the distributor belt wheels (50 and 100%), with 20 repetitions per treatment. In the second study, also in a completely randomized design were tested two planting speeds (5.0 and 6.5 km h-1) and two depths of furrow (0.35 and 0.45 m), with 20 repetitions. Finally, there was a case study to validate the disarm furrower system, as well as time and motion. The first study of the results show that the distribution system of the planter showed uniformity in the distribution wheels, with low damage to the gems. Increased working speed decreased the amount of grinding wheels, total and viable gems. And the increase of the rotating distributor conveyor raises these factors. In the second study, increased planting rate resulted in increased area and decreased mobilized mating height. The increased depth furrow caused increase in immobilized area, groove width, depth and furrow mating height. The planting operation kept uniform standards on the groove opening, distribution of seedlings and mating time in the planting depths and speed of operation. It was found that the furrower mechanism is able to disarm when encountering an obstacle, without any damage thereto. The time and motion study showed that for the beginning of a maneuver time was 11 s, 7.5 s of which was spent in the collection of the furrow openers, and the furrower maneuver on the end/start operation time is 11.2 s and 7.0 s of these expenditures to arm the furrowers early operation